Totally Contact Umbilical Lightlike Hypersurfaces of Indefinite -Manifolds - Rachna Rani; Rakesh Kumar; R. K. Nagaich (Journal of Mathematics)
We study totally contact umbilical lightlike hypersurfaces of indefinite -manifolds and prove the nonexistence of totally contact umbilical lightlike hypersurface in indefinite -space form.